Tourists’ Satisfaction with Key Coastal Tourism Destinations of West Bengal, India - Baitalik, Anirban; Majumder, Sankar; Bhattacharjee, Tanmoyee (Atna Journal of Tourism Studies, 2022)
This study is an attempt to analyse the satisfaction level of tourists’ visiting the popular coastal tourist destinations in the state of West Bengal in India. Simple checklist approach along with Likert scale techniques was employed as a response format to collect primary data from the sample of 300 tourists. Simple statistical techniques were used to analyse the so-collected data. This study indicate that the sample tourists were more satisfied with the scenic beauty of the places, transportation facilities, availability of food & beverages. They were also satisfied with the cleanliness, and accommodation facilities. But they were relatively less satisfied with the state of sanitation & safe drinking water, health facilities, and safety-security of the area. The study revealed that the marital status, household’s income, travel distance, and cost of accommodation had a significant positive association with the tourists’ satisfaction. Strangely, this study found significant negative association between per capita expenditure of the tourist and level of their satisfaction. This study revealed that the service-wise levels of satisfaction were highly sensitive to social, demographic as well as visitation characters of the tourists. It is expected that the findings of this study would be very useful in appropriate policy making for tourism development.